NILAI PENDIDIKAN BUDI PEKERTI DALAM NASKAH CERITA RAKYAT PRABU ANGLING DARMA - Kodrat Eko Putro Setiawan (UIN Fatmawati Sukarno Bengkulu, 2019)
The Value of Budi Pekerti Education in Prabu Angling Darma Folklore. Indonesia has various kinds of folklore that contain the values of ethic education. This study aims to describe the values of ethic education contained in the folklore of Angling Darma scipt. The method this study is descriptive qualitative. The object of this research is the East Java folklore manuscript Prabu Angling Darma. Data collection using reading and note taking techniques. Data analysis this study includes data reduction, data display, and conclusions. The results of this study are the values of ethic education contained in the text of the folklore Prabu Angling Darma among others : fair, trustworthy, honest, hard work, affection, forgiveness, patience, and tawadhu (hamble).